PERSEPSI LABA PEDAGANG KELONTONG PASAR RAKYAT BANYUASRI - Putu Eka Wati; Ni Wayan Yulianita Dewi; Putu Ria Astria (UNHI Press, 2023)
Abstract : The purpose of this study is to describe the meaning of profit according to grocery traders in the Banyuasri People's Market, Buleleng Regency. The selection of grocery traders in the Banyuasri People's Market in this study was based on the close relationship between the profession of grocery traders, with money and society. The profession of a grocer, money and society is an endless circle. All three are interrelated and related in various circles of life. There is a tool that brings the two parties together, namely